PENGOLAHAN MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI DESA KEMIRI SIDOARJO: SOLUSI KREATIF UNTUK LINGKUNGAN DAN EKONOMI LOKAL: PENGOLAHAN MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI DESA KEMIRI SIDOARJO: SOLUSI KREATIF UNTUK LINGKUNGAN DAN EKONOMI LOKAL - Budi Prabowo; Devi Diyah Ayu Prameswari; Laila Krisna Arti; Wandah Nur Aliyyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Careless disposal of waste can pollute the surrounding aquatic ecosystem. Therefore, innovative steps and solutions are needed to avoid random waste disposal in the environment around the community. Cooking activities that are carried out every day will definitely leave behind unused ingredients, one of which is cooking oil that has been used for frying activities. This cooking oil will become dangerous waste if thrown away carelessly. As a form of community service, group 5 of the National Defense KKN-T Wave 1, UPN "Veteran" East Java invites the community in Kemiri Village, Sidoarjo Regency, East Java to process used cooking oil waste from home into aromatherapy candles which can be developed as a product for entrepreneurship. The target of this activity is the community in RW 06 who are already superior in processing waste in the surrounding environment. This activity will include delivering material, a candle making demo, calculating COGS and how to brand a product. It is hoped that this community service work program can increase knowledge and build an entrepreneurial spirit to improve the village economy through waste that was previously considered worthless.